Embedding Finance in the Macroeconomics of Climate Change: Research Challenges and Opportunities Ahead - Irene Monasterolo (CESifo Forum, 2020)
The role of finance in the low-carbon transition, as well as the deep uncertainty and endogeneity of climate finance risk, are currently neglected by climate economic models. This leads to a false sense of control in terms of risks and opportunities associated with the low-carbon transition. Further, it prevents people from understanding under which conditions climate policies and finance could be a driver or a barrier. Recent research has started to shed light on how climate economic and financial risk modeling could embrace this complexity.
Keywords: 330